DDT, DDD, and DDE in soil of Xiangfen County, China: Residues, sources, spatial distribution, and health risks. (November 2016) - Ma, Jin; Pan, Li-bo; Yang, Xiao-yang; Liu, Xiao-ling; Tao, Shi-yang; Zhao, Long; Qin, Xiao-peng; Sun, Zai-jin; Hou, Hong; Zhou, Yong-zhang
Abstract: We collected and analyzed 128 surface soil samples from Xiangfen County for dichlorodiphenyltrichloroethane (DDT), dichlorodiphenyldichloroethane (DDD), and dichlorodiphenyldichloroethylene (DDE). Total DDT concentrations (DDTs; sum of p, p′ -DDD, p, p′ -DDE, and p, p′ -DDT) ranged from ND to 427.81 ng g −1 (dry weight, dw), with a mean of 40.26 ng g −1 (dw). Among the three compounds, p, p′ -DDD was the most dominant. The DDTs in Xiangfen County soils mainly originated from historical DDT use, but there were also new inputs likely related to dicofol use. The DDTs in Xiangfen County soils were mainly degraded under anaerobic conditions, and direct degradation to DDD was the main degradation route. Regions with relatively high concentrations of DDTs were mainly located in North and South Xiangfen County. In these regions, many soil samples contained p, p′ -DDT as the predominant pollutant, suggestive of extensive new inputs of DDT. A health risk assessment revealed that there are no serious long-term health impacts of exposure to DDTs in soil, for adults or children. Highlights: DDTs (sum of DDD, DDE, and DDT) residues were widely detected in soils. Dicofol was found to be important new inputs of DDTs. DDTs in soil does not have serious health impacts.